Experimental Investigation to Analyze the Mechanical and Microstructure Properties of 310 SS Performed by TIG Welding. (21st August 2022) - Goyal, Ashish; Kapoor, Hardik; Jayahari, Lade; Saxena, Kuldeep K; Salmaan, N. Ummal; Mohammed, Kahtan A.
Abstract : In present experimental work, 310 SS alloy has been welded by the TIG welding using design of experiment and grey relation optimization techniques. The input parameters, i.e., welding current, welding gas flow rate, and welding voltage, have been selected to perform the TIG welding. The same filler material was used during the welding process to investigate the mechanical and microstructure properties. The design of experiment and grey relation optimization techniques were used to optimize the effect on hardness and tensile strength of the welded joints. The experiments were performed as per the L9 orthogonal array obtained by the design of experiment methodology. The 65 A, 12 V, and 7.5 gas flow rate optimum setting of input parameters provides the better results for the effective hardness and tensile strength. The most significant parameters, i.e., welding current with 84.93% and welding voltage with 65.09%, were obtained for hardness and tensile strength, respectively.